Design of Education and Training for Instagram Mobile Application to Facilitate Digital M arketing for SMEs - Praptaningsih, Praptaningsih; Sunardi, Sunardi; Santosa, Eka Budhi (Universitas Sebelas Maret, 2023)
The rapid growth of social media and mobile applications, such as Instagram, has created significant opportunities for facilitating digital marketing for SMEs. The purpose of this research is to design and implement a specialized education and training program focusing on the use of the Instagram mobile application to facilitate digital marketing for SMEs. This study employs a qualitative descriptive approach to provide a comprehensive description of the design of education and training for the Instagram mobile application. Data collection techniques include observation and interviews with a sample of 10 respondents. The interview results indicate that with the appropriate resources, it is possible to expand marketing efforts and reach a larger number of potential customers. Active interaction and constructive feedback enhance the success of training and business growth through Instagram. The observations have resulted in an effective training design, where the training activities involve visual presentations, group discussions, and direct demonstrations. Participants practice using Instagram and then participate in a test followed by a group discussion. This research concludes that the training program successfully achieves its objectives, as participants engage in visual presentations, group discussions, and hands-on exercises using Instagram, while gaining the understanding and skills required for utilizing the platform.